The structure of affine buildings - Weiss, Richard M. (Richard Mark), 1946- (Princeton University Press, 2009)
Richard Weiss gives a detailed presentation of the complete proof of the classification of Bruhat-Tits buildings first completed by Jacques Tits in 1986. The book includes numerous results about automorphisms, completions and residues of these buildings.